Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/dvdy.20923
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of Tbx5‐induced genes expressed in the developing heart

Abstract: Tbx5 is a member of the T-box family of transcription factors and is associated with Holt-Oram syndrome (HOS), a congenital disorder characterized by heart and limb defects. Although implicated in several processes during development, only a few genes regulated by Tbx5 have been reported. To identify candidate genes regulated by Tbx5 during heart development, a microarray approach was used. A cardiacderived mouse cell line (1H) was infected with adenoviruses expressing Tbx5 or ␤-galactosidase and RNA was isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…Moreover, in a recent study, a gain of Tbx5 function in cultured cardiogenic cells revealed that an equivalent human mutant (R297er) alters the ability of Tbx5a to induce some but not all target genes (35). Finally, our results point to new sequences within the Tbx5 locus in which mutations may be associated with Holt-Oram syndrome or other congenital cardiac and/or limb defects.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Moreover, in a recent study, a gain of Tbx5 function in cultured cardiogenic cells revealed that an equivalent human mutant (R297er) alters the ability of Tbx5a to induce some but not all target genes (35). Finally, our results point to new sequences within the Tbx5 locus in which mutations may be associated with Holt-Oram syndrome or other congenital cardiac and/or limb defects.…”
Section: Discussionsupporting
confidence: 53%
“…6E). 35 S-labeled full-length GATA-4 (G4) (E) or wild-type (WT) and mutant Nkx2.5 proteins (F). Note how Tbx5b has a greatly reduced affinity for GATA-4, and note its inability to interact with Nkx2.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One microliter of synthesized cDNA was used for analysis by qRT-PCR (MJ Research Opticon 2). Gene expression levels determined by qRT-PCR were calculated as previously reported (24,37,45,46). A standard curve was generated for each experimental primer set with either E17.5 limbs or E13.5 whole embryo cDNA, and all the values were normalized to ribosomal protein L7 expression (17).…”
Section: Methodsmentioning
confidence: 99%
“…T-box genes encode transcription factors involved in the regulation of developmental processes, cell-cell signaling, negative regulation of cardiac muscle cell proliferation, induction of apoptosis and negative regulation of cell migration (He et al, 2002;Mori et al, 2006;Plageman and Yutzey, 2006;Maitra et al, 2009). This gene is located on human chromosome 12q24.1.…”
Section: Introductionmentioning
confidence: 99%